2017
DOI: 10.1097/wnp.0000000000000424
|View full text |Cite
|
Sign up to set email alerts
|

Interrater Agreement of EEG Interpretation After Pediatric Cardiac Arrest Using Standardized Critical Care EEG Terminology

Abstract: Purpose We evaluated interrater agreement of electroencephalography (EEG) interpretation in a cohort of critically ill children resuscitated after cardiac arrest using standardized EEG terminology. Methods Four pediatric electroencephalographers scored 10-minute EEG segments from 72 consecutive children obtained 24 hours after return of circulation using the American Clinical Neurophysiology Society’s (ACNS) Standardized Critical Care EEG terminology. The percent of perfect agreement and the kappa coefficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…[7][8][9][10] EEG data can be obtained noninvasively at the bedside and provide a standardized brain activity assessment, which may be useful in delineating the extent of brain injury. 11,12 When neurologists and intensivists predicted neurobehavioral outcomes from cardiac arrest cases, the addition of EEG data significantly improved prognostication accuracy. 13 Current practice involves EEG review by an electroencephalographer, and several EEG features have been associated with gross neurologic outcome at hospital discharge in children after cardiac arrest.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10] EEG data can be obtained noninvasively at the bedside and provide a standardized brain activity assessment, which may be useful in delineating the extent of brain injury. 11,12 When neurologists and intensivists predicted neurobehavioral outcomes from cardiac arrest cases, the addition of EEG data significantly improved prognostication accuracy. 13 Current practice involves EEG review by an electroencephalographer, and several EEG features have been associated with gross neurologic outcome at hospital discharge in children after cardiac arrest.…”
mentioning
confidence: 99%
“…13 Current practice involves EEG review by an electroencephalographer, and several EEG features have been associated with gross neurologic outcome at hospital discharge in children after cardiac arrest. [13][14][15][16][17][18][19][20][21][22][23][24][25][26] However, since visual EEG interpretation relies on qualitative interpretations by electroencephalographers, inter-rater agreement limitations 12,[25][26][27] may influence EEG-based neuroprognostication. 12,[25][26][27] Quantitative EEG (QEEG) analyses use computationally derived features that highlight specific components of EEG with numerical values.…”
mentioning
confidence: 99%
“…EEG background measures, including state changes, burst suppression, excess discontinuity and/or focal slowing, were not statistically different between the two groups, including initial cvEEG background pattern. [11, 12] All surviving patients were discharged home on anti-epileptic drugs (AEDs), with no difference between groups (Table 6).…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies of EEG monitoring in critically ill children have used this categorical system, 2022,32 and a prior study involving four pediatric electroencephalographers demonstrated almost perfect interrater agreement (kappa 0.89). 26 The EEG background was also combined into two background categories including: (1) favorable (normal or slow-disorganized categories), and (2) unfavorable (discontinuous/burst-suppression or attenuated-featureless categories).…”
Section: Methodsmentioning
confidence: 99%
“…To establish a standardized EEG analysis approach, we previously assessed the inter-rater agreement of standardized EEG variables. 25,26 However, a standardized EEG analysis approach also needs to determine when to assess the EEG and whether the EEG changes over time during the acute period. If the EEG is relatively stable during the acute period, then assessing the EEG during a single wide time span could be appropriate for subsequent prospective studies involving EEG assessment.…”
Section: Introductionmentioning
confidence: 99%